(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to evaluate the current state of integrating green education and environmental concebs into the curricula adopted for both basic and secondary education, and to assess their alignment with the strategic objectives of sustainable development . the study employed a comparative descriptive- analytical approach to review relevant educational literature and analyze curriculum content across different educational stages. The findings revealed varying levels of integration of environmental and sustainability-related concepts within the existing curricula. The study also identified a significant gap that requires particular attention between learners’ theoretical environmental knowledge and their actual sustainable behaviors. Furthermore, the results highlighted an urgent need to reform curricula in accordance with the green education model, emphasizing sustainable schools, project based environmental learning, the development of green skills, and the promotion of climate awareness. The study recommends the adoption of a national green education strategy that contributes to achieving the Sustainable Development Goals (SDGs) and enhancing the quality of education in Libya. It further advocates the implantation of the Green School model and the revision of curricula in line with UNESCO’s EDUCATION for Sustainable Development (ESD) standards and frameworks.